Functional cis-regulatory modules encoded by mouse-specific endogenous retrovirus - Vasavi Sundaram (Nature Portfolio, 2017)
The gene-battery model posits transposable elements (TEs) may becis-regulatory elements to control gene expression. Here, mouse-specific TEs are shown as binding sites for multiple collaborating transcription factors in embryonic stem cells, and act as cis-regulatory modules in synergistic fashion.